(untitled) (Journal of actual problems of jurisprudence, 2022)
The relevance of the topic of the article is due to the fact that at the beginning of the XXI century it is technological development that determines the competitiveness of the state, forms the conditions for economic growth, thereby ensuring the economic security of the state. The main author’s idea of this article was the assertion that the active development of the legal framework for ensuring the technological development of the Republic of Kazakhstan gives rise to problems of an institutional and legal nature that require resolution. The scientific significance of this study lies in the fact that the article offers the author’s interpretation of the investigated mechanism in structural terms. The practical significance lies in the focus on solving specific problems identified in the analysis process. Methodologically, the study was based on a systematic analysis, on the principle of a step-by-step solution of scientific and practical problems; the author of this article used the following research methods: the method of structuring the elements of complex social objects; method of systematization and analysis of the regulatory framework; methods of analysis and synthesis; design method and deduction method; methods of legal statics and methods of research of ratings. The main results of the study were the substantiation of the need to improve the mechanism of legal protection of technologies and technological innovations based on the analysis of the legal framework and the institutional structure of the mechanism under study. As a result, conclusions were formulated regarding the improvement of the legal framework for regulation, as well as the creation of a specially authorized government body to ensure the functioning of this mechanism. The value of the study is that its results are brought to the development of practical results, fused to improve the mechanism of legal protection of the economic security of the Republic of Kazakhstan in the context of increasing the technological competitiveness of the economy. The practical value of the conclusions and provisions of this article is confirmed by the fact that they can be used: 1) to develop further directions for improving the mechanism for the protection and protection of intellectual property rights in the technological development of the republic; 2) to amend the legislation governing this area of law and economic development of Kazakhstan. Key words: legal protection, mechanism, technologies, competitiveness, economic security.